Aristotle and crossing the boundaries between the sciences - Judson, L (De Gruyter, 2019)
On the basis of what Aristotle says in the Posterior Analytics about how sciences are differentiated and about the impermissibility (save in some exceptional cases) of ‘kind-crossing’, many commentators suppose that when it comes to his scientific practice, Aristotle treats the boundaries of the sciences as impermeable, so that if subject-matter X is the business of one science, it simply cannot (save for the exceptional cases) be the business of another. I call this the impermeable boundary theory of the sciences: knowledge is divided into watertight compartments, determined by their distinct genera, and what goes on in one compartment cannot turn up in another. I argue that, even if this is a correct account of Aristotle’s position in the Analytics, the view that he accepts the impermeable boundary theory when it comes to his scientific and philosophical work outside the Analytics is simply untenable.